Anesthesia for ERCP: Impact of Anesthesiologist's Experience on Outcome and Cost - Basavana G. Goudra; Preet Mohinder Singh; Ashish C. Sinha (Anesthesiology Research and Practice)
The present study evaluates the effect of anesthesiologist's experience in providing deep sedation for endoscopic retrograde cholangiopancreatography (ERCP) on cost and safety. Methodology. Perioperative records of 1167 patients who underwent ERCP were divided on the basis of anesthesiologist assisting these procedures either on regular basis (Group R) or on ad hoc basis (Group N). Comparisons were made for anesthesia times, complication rates, and airway interventions. Results. Across all American Society of Anesthesiologists (ASA) Classes, regular anesthesiologists were more efficient (overall mean anesthesia time in Group R was versus minutes in Group N). Within Group R, anesthesia times across all ASA classes were comparable. In Group N, anesthesia times for higher ASA status patients were significantly longer (ASA IV, versus ASA I, minutes). Intubation rates (0.76% versus 12.8%) and median minimal oxygen saturation (100% versus 97.01%) were significantly higher in Group R. Had Group R anesthesiologists performed all procedures, the hospital could have saved US $ 758536 (based upon operating room time costs). Conclusion. Experience in providing deep sedation improved patient safety and decreased the operating room turnaround time, thereby lowering operating room costs associated with these procedures.